Cancer and psychiatric diagnoses in the year preceding suicide - Geoffrey D. Kahn; Samantha H. Tam; Julia W. Felton; Joslyn Westphal; Gregory E. Simon; Ashli A. Owen‐Smith; Rebecca C. Rossom; Arne L. Beck; Frances L. Lynch; Yihe G. Daida; Christine Y. Lu; Stephen Waring; et al. (Cancer Medicine)
Abstract Background Patients with cancer are known to be at increased risk for suicide but little is known about the interaction between cancer and psychiatric diagnoses, another well‐documented risk factor. Methods Electronic medical records from nine healthcare systems participating in the Mental Health Research Network were aggregated to form a retrospective case–control study, with ICD‐9 codes used to identify diagnoses in the 1 year prior to death by suicide for cases (N = 3330) or matching index date for controls (N = 297,034). Conditional logistic regression was used to assess differences in cancer and psychiatric diagnoses between cases and controls, controlling for sex and age. Results Among patients without concurrent psychiatric diagnoses, cancer at disease sites with lower average 5‐year survival rates were associated with significantly greater relative risk, while cancer disease sites with survival rates of >70% conferred no increased risk. Patients with most psychiatric diagnoses were at higher risk, however, there was no additional risk conferred to these patients by a concurrent cancer diagnosis. Conclusion We found no evidence of a synergistic effect between cancer and psychiatric diagnoses. However, cancer patients with a concurrent psychiatric illness remain at the highest relative risk for suicide, regardless of cancer disease site, due to strong independent associations between psychiatric diagnoses and suicide. For patients without a concurrent psychiatric illness, cancer disease sites associated with worse prognoses appeared to confer greater suicide risk.